2008
DOI: 10.1111/j.1574-6968.2007.01064.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the mycobacterial glucosyl-3-phosphoglycerate synthase

Abstract: Mycobacteria synthesize unique polysaccharides that regulate fatty acid synthesis, namely the methylglucose lipopolysaccharide (MGLP) and the methylmannose polysaccharide. Glucosyl-(1-->2)-glycerate is found at the reducing end of MGLP. The mycobacterial gene encoding a glucosyl-3-phosphoglycerate synthase (GpgS), primarily found in actinobacteria and sharing very low amino acid identity with known homo-functional GpgSs, has been identified. This gene has been annotated as an inverting family 2 glycosyltransfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(91 citation statements)
references
References 25 publications
1
90
0
Order By: Relevance
“…The enzyme from M. burtonii was specific for GDP-glucose and despite the similarity of this substrate with GDP-mannose and of the reaction mechanism, GpgSs and MpgSs shared no sequence identity, save for short motifs. Remarkably, this GpgS also had very low amino acid sequence identity with the homo-functional GpgSs from mycobacteria [18]. On the other hand, the recombinant MpgP from M. burtonii dephosphorylated GPG to GG and MPG to MG. Due to the vicinity with the gpgS gene, it was designated gpgP.…”
Section: Pathways For the Synthesis Of Gg Glucosylglycerate Biosynthementioning
confidence: 94%
See 3 more Smart Citations
“…The enzyme from M. burtonii was specific for GDP-glucose and despite the similarity of this substrate with GDP-mannose and of the reaction mechanism, GpgSs and MpgSs shared no sequence identity, save for short motifs. Remarkably, this GpgS also had very low amino acid sequence identity with the homo-functional GpgSs from mycobacteria [18]. On the other hand, the recombinant MpgP from M. burtonii dephosphorylated GPG to GG and MPG to MG. Due to the vicinity with the gpgS gene, it was designated gpgP.…”
Section: Pathways For the Synthesis Of Gg Glucosylglycerate Biosynthementioning
confidence: 94%
“…The purification of the native enzyme allowed the identification of a highly divergent MpgS from which sequence homology to the known MpgSs had been extensively erased (Empadinhas et al, unpublished results). Adjacent to this mpgS gene we detected genes encoding two unspecific phosphatases, leading to the hypothesis that one or both could complete the two-step synthesis of MG. On the other hand, this atypical MpgS had high homology with one enzyme found in mycobacteria and related Actinobacteria, later found to be a glucosyl-3-phosphoglycerate synthase (GpgS) with low homology to the homo-functional GpgSs from M. burtonii and P. marina [8,9,18]. In fact, the R. xylanophilus MpgS could synthesize GPG, the phosphorylated precursor of GG, with higher efficiency than that for MPG, although free GG has never been detected in R. xylanophilus.…”
Section: The Ambiguous Mpgs From Rubrobacter Xylanophilusmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a wide range of halophilic microorganisms which comprise domains of Archaea and Bacteria. The saline cytoplasm of these bacteria requires enzymes which are rich in acidic amino acids and dependent on K+ or Na+ for their biological activity [3]. Oren and Mana 2002 [4] have reported that these organisms include: (i) the extremely halophilic Archaea of the family Halobacteriaceae, which comprises Halobacterium, Haloarcula, Haloquadratum, Halorhabdus, Natronobacterium and Natronococcus (ii) the halophilic Bacteria of the order Haloanaerobiales and (iii) the bacterium S. ruber.…”
Section: Introductionmentioning
confidence: 99%